Retention of β -Carotene from Leafy Vegetables - Nara, Haribhau (Plantae Scientia, 2020)
During the present investigations, effect of table salt on retention of β-carotene from leafy vegetables from Marathwada was studied. Getting vegetables throughout the year is obscure in rain feed area like Marathwada. Retention of nutrition from vegetables is important for health in absence of in adequate preservation techniques. Five different green leafy vegetables which are consumed by the peoples on large scale have been tried during the present piece of work. These vegetables are Spinach (Spinacia oleracea L.), Coriander (Coriandrum sativum L.), fenugreek (Trigonella foenum-graecum L.), Shepu (Anathum graveolens L.) and Cabbage (Brassica oleracea var. capitata L.) which are commonly consumed in Marathwada region. These vegetables were soaked with solution of common Table salt i.e. Sodium Chloride (NaCl2) at different concentrations. After analysis it was noted that in Spinach, Coriander, Trigonella and Anthem. The results obtained during the work clearly indicate that, the common salt can act as excellent preservative for retention of β-carotene from leafy vegetables.